Effect of Volatile Organic Compounds from Branches of Healthy and Unhealthy Araucaria araucana (Molina) K. Koch Trees on Host Selection by Bark Beetle Sinophloeus porteri (Coleoptera: Curculionidae) - Washington Aniñir; Leonardo Bardehle; Cristian Montalva; Andrés Quiroz; Javier Espinoza (Insects)
Araucaria araucana is one of the longest-living Chilean trees. Recently, Araucaria Leaf Damage disease, which causes damage to branches and crowns, was detected. Sinophloeus porteri, a bark beetle affecting A. araucana, could be associated with foliar damage. However, little is known about their ecological and chemical interactions. This study examined the olfactory response of S. porteri to volatiles emitted from A. araucana. Branches and weevils were collected from a national park, and volatiles were trapped from both healthy and unhealthy branches. Thirty terpenes were identified, some of which were reported for the first time in A. araucana. Healthy branches emitted large amounts of myrcene (>360 ng g−1 day−1), and unhealthy branches showed high hibaene emanations (>140 ng g−1 day−1). Olfactory assays verified that S. porteri was attracted to the volatile blends of branches, regardless of the health condition of the branches, but preferred the blend of unhealthy branches. Moreover, myrcene was repellent to these weevils, and hibaene acted as an attractant, suggesting that A. araucana might use myrcene for defense against S. porteri, and hibaene could stimulate host selection by beetles.